Development of Learning Media for Digital Comics Based on a Contextual Approach to Increase Learning Motivation in Optical Instruments - Mustika Zahfira Utami (IJOEM: Indonesian Journal of E-learning and Multimedia, 2022)
This study aims to describe the feasibility and characteristics of digital comic learning media based on a contextual approach to increase learning motivation on the material of optical instruments and get a good perception of readability from students. This research is a research and development (R&D) with a 3D model with the steps to define, design, and develop. Data collection techniques are non-test techniques that use observation data, document review, and questionnaires. Data analysis techniques are descriptive, qualitative, and quantitative methods. The subjects used in this study were physics teachers and students of class XII in SMA Negeri 2, 4, and 9 Bengkulu City. The results of this study can be concluded that the digital comic learning media developed is included in the very feasible criteria with an average percentage of 90.41% and has the characteristics of a contextual approach and learning motivation so that it deserves to be tested and gets a very good perception from students of the readability of comic learning media digital with an average percentage of 85.70%.